2022
DOI: 10.1097/ncq.0000000000000619
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the US News and World Report–Calculated Nurse Staffing Index With Actual Hospital-Reported Nurse Staffing

Abstract: N ursing care is a fundamental aspect of effective, efficient, and safe health care. Over the past several decades, there has been considerable debate about how to best define, measure, and incorporate nurse staffing levels into clinical practice and health policy decisions. [1][2][3] Nevertheless, nurse staffing levels have been used by oversight organizations, in public policy legislation, and in hospital rankings as a proxy for the quality of nursing care. 4,5 One of the most visible examples is the US News… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The weak correlation between FTE midwives and ward HPPD is interesting as we expected this to be more closely related. However, this is not an unusual finding as recent research from the USA has also discovered differences in the performance of staffing measures, and called for validated measures to be used [ 44 ]. The weak correlation may be due to the fact that postnatal services are not always prioritised [ 45 ], or that Trusts employing a large number midwives may have additional services such as fetal medicine or midwives in specialist roles.…”
Section: Discussionmentioning
confidence: 99%
“…The weak correlation between FTE midwives and ward HPPD is interesting as we expected this to be more closely related. However, this is not an unusual finding as recent research from the USA has also discovered differences in the performance of staffing measures, and called for validated measures to be used [ 44 ]. The weak correlation may be due to the fact that postnatal services are not always prioritised [ 45 ], or that Trusts employing a large number midwives may have additional services such as fetal medicine or midwives in specialist roles.…”
Section: Discussionmentioning
confidence: 99%
“…The weak correlation between FTE midwives and ward level CHPPD is interesting as we expected this to be more closely related. However, this is not an unusual finding as recent research from the USA has also discovered differences in the performance of staffing measures, and called for validated measures to be used[34] Winter et al[23] found that estimates of staffing and outcomes were larger and more precise when data is disaggregated. This has not been found in our study despite the expectation of gaining more clarity with localised data at a ward level.…”
Section: Discussionmentioning
confidence: 99%